Short-Term Immobilization Promotes a Rapid Loss of Motor Evoked Potentials and Strength That Is Not Rescued by rTMS Treatment - Gaffney, Christopher J.; Drinkwater, Amber; Joshi, Shalmali D.; O'Hanlon, Brandon; Robinson, Abbie; Sands, Kayle-Anne; Slade, Kate; Braithwaite, Jason J.; Nuttall, Helen E. (Frontiers in Human Neuroscience, 2021)
Short-term limb immobilization results in skeletal muscle decline, but the underlying mechanisms are incompletely understood. This study aimed to determine the neurophysiologic basis of immobilization-induced skeletal muscle decline, and whether repetitive Transcranial Magnetic Stimulation (rTMS) could prevent any decline. Twenty-four healthy young males (20 ± 0.5 years) underwent unilateral limb immobilization for 72 h. Subjects were randomized between daily rTMS (n = 12) using six 20 Hz pulse trains of 1.5 s duration with a 60 s inter-train-interval delivered at 90% resting Motor Threshold (rMT), or Sham rTMS (n = 12) throughout immobilization. Maximal grip strength, EMG activity, arm volume, and composition were determined at 0 and 72 h. Motor Evoked Potentials (MEPs) were determined daily throughout immobilization to index motor excitability. Immobilization induced a significant reduction in motor excitability across time (−30% at 72 h; p < 0.05). The rTMS intervention increased motor excitability at 0 h (+13%, p < 0.05). Despite daily rTMS treatment, there was still a significant reduction in motor excitability (−33% at 72 h, p < 0.05), loss in EMG activity (−23.5% at 72 h; p < 0.05), and a loss of maximal grip strength (−22%, p < 0.001) after immobilization. Interestingly, the increase in biceps (Sham vs. rTMS) (+0.8 vs. +0.1 mm, p < 0.01) and posterior forearm (+0.3 vs. +0.0 mm, p < 0.05) skinfold thickness with immobilization in Sham treatment was not observed following rTMS treatment. Reduced MEPs drive the loss of strength with immobilization. Repetitive Transcranial Magnetic Stimulation cannot prevent this loss of strength but further investigation and optimization of neuroplasticity protocols may have therapeutic benefit.